Paediatric antiepileptic polytherapy: systematic review of efficacy and neurobehavioural effects and a tertiary centre experience. (23rd April 2018) - Plevin, D; Jureidini, J; Howell, S; Smith, N
Abstract: Aim: This paper presents the prevalence of antiepileptic polytherapy at a single tertiary institution and systematically reviews the evidence base for its efficacy and neurobehavioural safety in children. Method: Prevalence of antiepileptic polypharmacy was determined from pharmacy dispensing records at a paediatric tertiary hospital and neurobehavioural comorbidities quantified through casenote review; comparison is made with studies evaluating the neurobehavioural safety of antiepileptic polytherapy, identified via systematic literature review. Results: Amongst 262 patients at the hospital, 117 (44.7%) were prescribed polytherapy; with patients having an intellectual disability statistically more likely to be prescribed polytherapy than those without (70.5% vs 40.6%; p < 0.0001). Systematic review identified no trials addressing the efficacy or neurobehavioural outcomes of polytherapy as a primary outcome. Several observational studies identified associations between polytherapy and neurobehavioural adverse outcomes such as anxiety and behavioural disturbance. Observational studies also suggest that a reduction in polytherapy load is generally not associated with worsening seizure control. Conclusion: Whilst antiepileptic polytherapy is common practice within paediatric epilepsy cohorts attending tertiary care institutions, evidence is lacking to support its efficacy. There are significant practical difficulties to undertaking randomised controlled trials within this population. Nonetheless, clinicians must consider that adverse neurobehavioural consequences of polytherapy might outweigh benefits to seizure control.